Registration of two oilseed sunflower germplasms HA‐DM7 and HA‐DM8 resistant to sunflower downy mildew. Issue 2 (16th February 2022) - Ma, Guojia; Seiler, Gerald; Qi, Lili
Abstract: Downy mildew (DM) is one of the most destructive diseases in sunflower ( Helianthus annuus L.) production worldwide that limits yield and reduces seed quality. The oilseed sunflower germplasms HA‐DM7 (Reg. no. GP‐375, PI 691508) and HA‐DM8 (Reg. no. GP‐376, PI 698192) were developed using backcrossing, pedigree breeding, and DNA marker‐assisted selection for DM resistance. They were released by the USDA‐ARS, Sunflower and Plant Biology Research Unit in collaboration with the North Dakota Agricultural Experiment Station in July 2019 and March 2020, respectively. HA‐DM7 is a BC2 F3 ‐derived BC2 F4 oilseed maintainer selection from the cross of HA 89*2//NMS HA 89/PI 494578, and HA‐DM8 is a BC2 F5 ‐derived BC2 F6 oilseed maintainer selection from the cross of HA 89*2//NMS HA 89/PI 494576. HA‐DM7 harbors the DM R gene Pl20 mapped to sunflower chromosome 8, while HA‐DM8 harbors the DM R gene Pl35 on sunflower chromosome 1. Both genes were derived from wild sunflower species Helianthus argophyllus accessions, PI 494578 and PI 494576, respectively, both having broad‐spectrum resistance to the most predominant and virulent Plasmopara halstedii races identified in North America and Europe. Phenotypic and molecular testing confirmed that HA‐DM7 and HA‐DM8 germplasms are homozygous for the DM gene. These DM‐resistant oilseed sunflower germplasms will expand the genetic pool for sunflower breeding projects globally, protecting sunflower production from yield losses. Core Ideas: Resistance in HA‐DM7 and HA‐DM8 was introduced from wild sunflower species Helianthus argophyllus . HA‐DM7 and HA‐DM8 harbor the downy mildew R genes Pl20 and Pl35, respectively. Two lines exhibit resistance to the most prevalent and virulent downy mildew races. These interspecific germplasms will broaden the genetic base of cultivated sunflower.